Knowledge gaps about the diagnosis and treatment of hypothyroidism: an international patient survey - Perros, Petros; Poots, Alan; Nagy, Endre Vezekenyi; Papini, Enrico; Hay, Harriet; Abad-Madroñero, Juan; Tallett, Amy; Lakwijk, Petrus; Hegedüs, Laszlo (Frontiers in Endocrinology, 2025)
IntroductionOver-diagnosis and over-treatment of hypothyroidism is a growing concern. The role of patient knowledge has not been previously investigated. The aim was to explore patient knowledge in relation to diagnosis and treatment of hypothyroidism.MethodsCross-sectional, international online survey. Participants were people with treated hypothyroidism amounting to 3421 valid respondents from 68 countries. A questionnaire was used, which included knowledge statements about hypothyroidism relating to recommendations by international guidelines. The principal knowledge statement was “A patient with a normal thyroid blood test does not need to be treated with thyroid hormones (even if they have positive thyroid antibodies and symptoms)”, and participants were asked to classify it as “false”, “true”, or “don’t know”. Responses were divided into corresponding groups: “Incorrect”, “Correct”, and “Unsure”. Associations of groups with respondent characteristics and patient reported outcomes were investigated. Responses to a further seven knowledge statements explored ampliative knowledge about hypothyroidism.ResultsWith regards to the principal knowledge statement, “Correct”, “Incorrect” and “Unsure” comprised 15.3%, 50.7% and 34.0% of responses to the respectively. “Incorrect” respondents were more likely than expected to live in the United Kingdom, have Hashimoto’s thyroiditis, have a recent low self-reported serum thyrotropin, be treated with liothyronine-containing medication, and use social media and the internet for hypothyroidism-related information daily. “Incorrect” responses were associated with dissatisfaction, poor perceived control of symptoms and negative impact of hypothyroidism on everyday activities. The proportion of “Incorrect” responses for seven other knowledge statements ranged between 1.8-34.9%.DiscussionIncorrect responses to the principal knowledge statement were common in this sample of people with hypothyroidism, and associated with several demographic variables and adverse patient outcomes. Our findings suggest that knowledge gaps about the significance of symptoms in relation to the diagnosis and treatment of hypothyroidism may be important in driving over-diagnosis and over-treatment. The high number of “Unsure” respondents suggests that patient education may be an effective intervention.